Kinetic and Mechanistic Studies in the Oxidation of n-Butanol by p-Methoxy-N-bromobenzamide - Badole, M.K.; Malviya, L.N.; Siriah, V.K. (Asian Journal of Chemistry, 2012)
Kinetics studies of the oxidation of n-butanol by p-methoxy-N-bromobenzamide has been made in aqoues acetic acid in presence of mercuric acetate. The reaction is first order with respect to both, the oxidant and near about are with respect to the substrates. The order with respect to perchloric acid is fractional or first order depending upon the substrate concentration. The reaction is retarded by the initial addition of benzamide and is enhanced by the added potassium bromide. The activation parameters have been calculated and a suitable mechanism has been proposed.